MEKANISME IMUNOLOGI DARI RESISTENSI DOMBA EKOR TIPIS TERHADAP INFEKSI Fasciola gigantica - Ening Wiedosari (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Previous studies shown that Indonesian Thin-Tailed (ITT) sheep are more resistant to infection than Merino sheep infected with Fasciola gigantica. Eosinophils isolated from ITT sheep between 2-6 weeks postinfection could effectively kill immature parasites in vitro by superoxide radicals produced by these cells. The present study was undertaken to identify immunological mechanisms associated with such resistance by comparison of immue responses to fluke antigen in ITT and Merino sheep, a breed susceptible to infection with F. gigantica. This knowledge will enable the development of targeted control strategies using immunomanipulation such as by vaccination.Two critical observations from this in vivo studies were made including (1) eosinophils were significantly elevated at the time of F. gigantica parasite killing in the ITT host relative to the F. giganfi'ca-susceptible Merino host, (2) IgG, responses correlated with resistance to infection in the ITT host.